2007
DOI: 10.1161/circulationaha.106.681072
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of the Sympatho-Adrenergic System in Regulating Valve Calcification

Abstract: Background-Aortic valve calcification is a progressive process resembling ossification. Recent evidence indicates that the sympathetic nervous system plays an important role in regulating bone deposition and resorption through the ␤ 2 -adrenergic receptors (␤ 2 -ARs). The aim of this study is to determine the level and pattern of expression of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Because elevated periostin expression is present following adult myocardial hypertrophy, 10 infarction, 27 arterial injury, 15 and valve calcification, 28 we examined its expression in both normal and heart failure models to assess when and where periostin elevation occurs. To efficiently distinguish cardiomyocytes from the noncardiomyocyte cells, we made use of the ␣MHC-EGFP reporter mice 19 expressing EGFP exclusively in cardiac muscle.…”
Section: Periostin Is Absent From Cardiomyocytes But Is Expressed Thrmentioning
confidence: 99%
“…Because elevated periostin expression is present following adult myocardial hypertrophy, 10 infarction, 27 arterial injury, 15 and valve calcification, 28 we examined its expression in both normal and heart failure models to assess when and where periostin elevation occurs. To efficiently distinguish cardiomyocytes from the noncardiomyocyte cells, we made use of the ␣MHC-EGFP reporter mice 19 expressing EGFP exclusively in cardiac muscle.…”
Section: Periostin Is Absent From Cardiomyocytes But Is Expressed Thrmentioning
confidence: 99%
“…The previous studies conducted on VHD have largely been observational, immunohistologic, and in vitro studies (8)(9)(10)(11)(12)(13). Although the onset of aortic valve stenosis has been reported in Smad6-deficient mice (14), in fibulin 4-deficient mice (15), and in humans with the NOTCH1 mutation (16), the abnormality has primarily been observed during cardiac valve development.…”
Section: Introductionmentioning
confidence: 99%
“…NE can cause a potent contraction of smooth muscle cells through the stimulation of specific receptor subtypes in equine aortic valve 9,10 . There are more known adrenoceptor subtypes, a number of which have been found in human heart valve tissue: α1, α2, β1 and β2 adrenoceptors 10,11 . Williams TH et al 3 reported that rat mitral valves had been shown to display spontaneous contraction-like movements localized to the leaflet itself, immediately after being dissected from the heart, which was enhanced by addition of norepinephrine (NE) in a dose-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%